Leituras brasileiras sobre a nova ordem internacional (1989-1994) - Ribeiro, Andrea Oliveira (2011)
This study is the result of a research conducted on Brazilian readings about the New World Order. I tried to analyze - based on historical sources of Centro de Pesquisa e Documentação em História Contemporânea do Brasil (CPDOC/FGV), such as Marcílio Marques Moreira File textual documents and Celso Amorim, Celso Lafer, Gelson Fonseca e Luiz Felipe Lampreia’s interviews - the main ideas of three historical personalitites directly involved in the formulation of Brazilian foreign policy during the New Republic, more specifically between 1989 and 1994. These three personalities are Celso Lafer, Gelson Fonseca e Rubens Ricupero. To this purpose, I try to highlight the main ways of interpreting the international system changed by the end of the 'bipolar conflict' with the support of most recent literature produced in the area, with the studies of Odd Westad (2005), Andrew Hurrell (2001, 2007) and John Ikenberry (2005). The data gathered during the research process allows us to assert that, in Brazil, the themes of autonomy and development are resilient. Debates about autonomy and development - so important to academic and political discourse developed in the 50’s – not only remained as major concern in foreign policy makers’ analysis, but also shows that, in Brazil, the discourse of modernization has reprised the basic ideas of local political thought.